Reaksi Hidrorengkah n-Heksadeka Menggunakan Katalis Nikel-Zeolit Alam Serta Penentuan Energi Aktivasi (Ea) dan Orde Reaksi - Ilham Salim; Yohanes B.J. Rusmanta; Jukwati Jukwati (Jurnal Penelitian Pendidikan IPA, 2022)
Research has been carried out on the preparation of active natural zeolite impregnated with nickel followed by activity testing through the hydrocracking catalytic reaction of n-Hexadecane. Active natural zeolite was obtained from PT Prima Zeolita Yogyakarta. The nickel concentration in the zeolite sample was carried out by ion exchange method with [Ni(NH3)6]2+ precursor solution with a concentration of 0.06M. The nickel content of the catalyst was determined by Atomic Absorption Spectrophotometer (AAS). The hydrocracking reaction used a fixed bed reactor system. Ratio of feed (n-Hexadecane) : catalyst = 3 : 1 (in gram). Catalysis study also carried out at various temperatures, from 315oC - 450oC at Â certain nickel content. Â The results of the catalytic reaction at each temperature after passing through the cooling system there was a liquid fraction that had been successfully accommodated then weighed and determined the percent of conversion. Furthermore, for the determination of Ea and the order of the reaction using linear regression calculations. The results showed that the catalytic reaction using an active natural Ni-Zeolite catalyst in the n-Hexadecane hydrocracking process resulted in different conversion results depending on the temperature of the catalytic reaction. The largest conversion was obtained at a temperature of 450oC, which was 35.18%. The reaction order was the first-order reaction (n=1). Meanwhile, the activation energy or activation energy (Ea) of the catalytic reaction in the n-Hexadecane hydrocracking process using a natural Ni-Natural zeolite catalyst with a nickel content of 2.0% (w/w) was 127.071 kJmol-1.